High Expression F2-Isoprostan (F2-IsoP), High Sterol Regulatory Element Binding Protein-2 (SREBP-2) and Low 2-Methoxyestradiol (2-ME) On Placenta Tissue as a Risk Factor of Pre-Eclampsia - Jaya Kusuma AAN; Suwiyoga K; Mantik AN; Sukrama DM (Journal of Global Pharma Technology, 2017)
To date, pre-eclampsia (PE) still a problem of Maternal Fetal Medicine related to high incidence, maternal and neonatal morbidity and mortality. Pre-eclampsia is caused by pregnancy; however, the mechanism has not been established so it is still a disease of theories. This relates to differences in treatment, resulting in different ways of prevention and output of PE itself. Recently, the role of F2-IsoP ,SREBP-2 and 2-ME was suspected to be very important in the mechanism of the PE. Meanwhile, the placenta acts as a source regulatory protein production, so that the material of this study was taken from placental tissue. The study objective was to prove the high F2I-soP, high SREBP-2 and low 2-ME expression in the placenta as risk factors for PE Case control study has been conducted in the department of obstetrics and gynecology Sanglah Hospital with 62 samples in 2015. The case group consisted of 31 mothers with PE and control groups consisted of 31 non-PE mother. The study material is a placental tissue. F2-IsoP and SREBP-2 expression study was performed using immunohistochemistry and 2-ME with ELISA techniques in Pathobiology Laboratory Faculty of Veterinary Medicine Udayana University. Data were analyzed with chi square test and discriminant using SPSS. The statistical test results are presented in tabular form and narrative. In this study, it was found that high expression of F2-IsoP increased the risk of PE 4 times higher (OR = 4.44; 95% CI = 1.53 to 12.94; p = 0.005) ; high expression of SREBP-2 increased the risk of PE 8 times higher (OR = 8.19, CI95% = 2,311 to 29.073; p = 0.001) and low expression of 2-ME increased the risk of PE 5 times higher (OR = 5.23; CI95% = 1.75 to 15.55; p = 0.002). On the discriminant test, we obtained contributing risk factor for the occurrence of PE were SREBP-2, F2Isop and 2-ME (p = 0.002) respectively. Conclusion, high F2-IsoP expression, high SREBP-2 expression and low 2-ME expression in placenta were risk factors for PE. The most dominant risk factor of PE mechanism was SREBP-2.Keywords: Pre-eclampsia, F2-Isoprostane, Sterol Regulatory Element Binding Protein-2, 2-Methoxyestradiol.